PMO-072 A 1 year two phase prospective project looking at nutritional risk in reactive vs elective nasogastric enteral feeding in head and neck cancer patients undergoing radical (chemo)radiotherapy. (28th May 2012) - Sheth, C H; Sharp, S; Baughan, C; Walters, E
Abstract : Introduction: Pre 2009 head and neck cancer (HNC) patients requiring enteral tube feeding during radical (chemo)radiotherapy at our regional cancer centre were admitted reactively in a nutritional "crisis" and fed via a nasogastric(NG) tube. 1 Audit resulted in a 1-year service improvement grant for a Specialist Dietitian to proactively support HNC patients "from pre-treatment until rehabilitation is complete". 2 The aim of this 1-year (2009–2010) two-phase prospective project was to reduce nutrition related crisis admissions, malnutrition and refeeding syndrome, thereby reducing length of hospital stay (LOS) from an average of 13 days 1 while aiming to improve patient experience and outcome. Methods: Phase1 (9 months): All patients with HNC (squamous cell carcinoma) were included. Nutritional status (MUST score), %weight loss and swallow ability was recorded for all patients before, during and after radiotherapy treatment. Patients were admitted reactively with inadequate nutritional intake and/or 5% weight loss. Interim review of phase 1 highlighted that oral cavity, oropharyngeal, nasopharyngeal, hypopharyngeal carcinomas and unknown primary tumours were at nutritional risk from weeks 2 and 3 of radiotherapy, leading to reactive admissions for NG feeding. Phase 2 (3 months) involved patients with these tumours admitted electively for NG feeding in week 3 radiotherapy. All admitted patients were followed up for 6 months. Results: Refeeding risk, number of days until nutritionally fit and LOS were all significantly reduced in phase 2 compared to phase 1. Conclusion: This data demonstrates that when appropriately funded, a specialist dietetic service working as part of a multidisciplinary team in HNC, by electively admitting high nutritional risk patients for NG feeding, can significantly reduce clinical risk and costs. As a result of clinical benefits and cost savings our Trust made the service improvement funding substantive. Competing interests: None declared. References: 1. Sheth CH, Sharp S, Walters E. A two year audit of enteral feeding in head and neck cancer patients receiving radiotherapy or chemoradiotherapy treatment at a UK Cancer Centre. 2011. Article submitted for publication. 2. National Institute for Clinical Excellence . Improving Outcomes for Head & Neck Cancer . London: NICE, 2004.